Kinetic field theory: effects of momentum correlations on the cosmic density-fluctuation power spectrum - Bartelmann, Matthias; Fabis, Felix; Kozlikin, Elena; Lilow, Robert; Dombrowski, Johannes; Mildenberger, Julius (New journal of physics, 2017)
In earlier work, we have developed a kinetic field theory (KFT) for cosmological structure formation and showed that the nonlinear density-fluctuation power spectrum known from numerical simulations can be reproduced quite well even if particle interactions are taken into account to first order only. Besides approximating gravitational interactions, we had to truncate the initial correlation hierarchy of particle momenta at the second order. Here, we substantially simplify KFT. We show that its central object, the free generating functional, can be factorised, taking the full hierarchy of momentum correlations into account. The factors appearing in the generating functional, which we identify as nonlinearly evolved density-fluctuation power spectra, have a universal form and can thus be tabulated for fast access in perturbation schemes. In this paper, we focus on a complete evaluation of the free generating functional of KFT, not including particle interactions yet. This implies that the nonlinearly evolved power spectra contain a damping term which reflects that structures are being wiped out at late times by free streaming. Once particle interactions will be taken into account, they will compensate this damping. If we suppress this damping in a way suggested by the fluctuation-dissipation relations of KFT, our results show that the complete hierarchy of initial momentum correlations is responsible for a large part of the characteristic nonlinear deformation and the mode transport in the density-fluctuation power spectrum. Without any adjustable parameters, KFT accurately reproduces the scale at which nonlinear evolution sets in. Finally, we further develop perturbation theory based on the factorisation of the generating functional and propose a diagrammatic scheme for the perturbation terms.
Gesehen am 14.09.2017